2021
DOI: 10.3389/fcell.2021.625680
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Physical Training on Exercise-Induced Inflammation and Performance in Mice

Abstract: Acute exercise increases the amount of circulating inflammatory cells and cytokines to maintain physiological homeostasis. However, it remains unclear how physical training regulates exercise-induced inflammation and performance. Here, we demonstrate that acute high intensity exercise promotes an inflammatory profile characterized by increased blood IL-6 levels, neutrophil migratory capacity, and leukocyte recruitment to skeletal muscle vessels. Moreover, we found that physical training amplified leukocyte–end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…In this context, clinical studies have shown that regular physical exercise in the form of high‐intensity interval training (HIIT) and continuous training (CT) can prevent pathological diseases, including pulmonary and cardiovascular diseases, diabetes mellitus, metabolic syndrome and cases associated with systemic inflammation (Amirazodi et al., 2022 ). Accordingly, exercise‐induced biochemical changes increase the amount of circulating inflammatory cells and cytokines to maintain physiological homeostasis (Barcellos et al., 2021 ), and antioxidant increases are associated with post‐exercise immune system changes (cell adhesion, lymphocyte proliferation and inflammation). Previous studies have supported that CT increases the efficiency of immune function, decreases serum levels of markers of inflammation, and also suppresses nuclear factor‐κB (NF‐κB) signalling and its proinflammatory targets interleukin (IL)‐6 and TNF‐α in rats (Liu & Chang, 2018 ; Petersen & Pedersen, 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“…In this context, clinical studies have shown that regular physical exercise in the form of high‐intensity interval training (HIIT) and continuous training (CT) can prevent pathological diseases, including pulmonary and cardiovascular diseases, diabetes mellitus, metabolic syndrome and cases associated with systemic inflammation (Amirazodi et al., 2022 ). Accordingly, exercise‐induced biochemical changes increase the amount of circulating inflammatory cells and cytokines to maintain physiological homeostasis (Barcellos et al., 2021 ), and antioxidant increases are associated with post‐exercise immune system changes (cell adhesion, lymphocyte proliferation and inflammation). Previous studies have supported that CT increases the efficiency of immune function, decreases serum levels of markers of inflammation, and also suppresses nuclear factor‐κB (NF‐κB) signalling and its proinflammatory targets interleukin (IL)‐6 and TNF‐α in rats (Liu & Chang, 2018 ; Petersen & Pedersen, 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that the exacerbation of behavioral impairments induced by a combination of RS + ES is unlikely to be mediated through triggering these pro‐inflammatory biomarkers. Although an imbalance involving excessive exercise and inadequate recovery increases the production and release of pro‐inflammatory cytokines, initiating most of the signs and symptoms linked to performance decrement (da Rocha et al., 2019; de Barcellos et al., 2021), there is a paucity of studies evaluating its impact on maternal and neonatal inflammatory status and related neurobehavioral outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of this, prenatal zinc supplementation unexpectedly did not result in any improvement in behavioral and inflammatory consequences induced by the combination of RS and ES. As strenuous exercise alters blood immune and inflammatory profiles (Cerqueira et al., 2019; da Rocha et al., 2019; de Barcellos et al., 2021), it can increase the amount of circulating inflammatory cells and cytokines to maintain physiological homeostasis (Cerqueira et al., 2019; da Rocha et al., 2019; Ostrowski et al., 1999; Suzuki et al., 2002), which may mask or conceal the suppression effect of zinc on PS‐induced pro‐inflammatory responses.…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Libardi et al, the final blood sample was collected seven days following the last exercise session, and in the study by Eaton et al the final blood samples were taken just three hours after exercise intervention (27,28). It has been revealed that acute exercise increases the release of inflammatory indices (29). In addition, the difference in participants and baseline values of the variables can also explain the discrepancy, so that in the research by Libardi et al, the participants were healthy individuals with normal baseline values of the inflammatory cytokines (27).…”
Section: Discussionmentioning
confidence: 99%